Behind influencer marketing: key marketing decisions and their effects on followers' responses - Martínez-López, Francisco J.; Anaya-Sánchez, Rafael; Fernández Giordano, Marisel; Lopez-Lopez, David (Journal of marketing management, 2020)
Influencer marketing actions are mostly carried out on social platforms, e.g., Facebook, Instagram and Twitter. However, despite its increasing use, studies on this subject are still scarce. In this research, we focus on four essential factors related to an influencer marketing programme, analyzed in two separate experimental studies for theoretical reasons and methodological operability: brand control over the shared message and its commercial orientation; and, the celebrity level of the influencer and his/her congruence with the product/service they comment on in the post. We are also interested in the effects of these factors on a set of key responses by the follower with regard to the elements that form part of an influencer marketing action: the influencer, the post, and the product/service.